Economics - Hall, Robert E. (Thomson/South-Western, 2008)
Because issues of policy and real applications are critical to the principles of economics course, acclaimed economists Hall and Lieberman have made the latest edition of their cutting-edge text as current as today's headlines, giving students a real-world, up-to-the-minute overview that presents economics as a unified discipline. Taking a no-nonsense, policy approach to economic theory and application, this comprehensive text is very accessible, equipping readers with a solid foundation in economics that they can build upon wherever their career paths may lead. A wealth of interactive online exercises, graphing applications, and research opportunities give students hands-on experience working with current economic issues. Hall and Lieberman's careful focus on core theoretical ideas and systematic application of theoretical tools to timely, practical questions conveys the message that economics is an integrated, powerful body of knowledge that can effectively address domestic and global issues.